An experimental determination of the drag coefficient of a Mens 8+ racing shell - Buckmann, J. G.; Harris, S. D. (SpringerPlus, 2014)
This study centered around an experimental analysis of a Mens Lightweight Eight racing shell and, specifically, determining an approximation for the drag coefficient. A testing procedure was employed that used a Global Positioning System (GPS) unit in order to determine the acceleration and drag force on the shell, and through calculations yield a drag coefficient. The testing was run over several days in numerous conditions, and a 95% confidence interval was established to capture the results. The results obtained, over these varying trials, maintained a successful level of consistency. The significance of this study transcends the determination an approximation for the drag coefficient of the racing shell; it defined a successful means of quantifying performance of the shell itself. The testing procedures outlined in the study represent a uniform means of evaluating the factors that influence drag on the shell, and thus influence speed.